2016
DOI: 10.1186/s12894-016-0169-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of the antibiotic regimen in transrectal ultrasound-guided biopsy: quinolone versus cephalosporin

Abstract: BackgroundQuinolone is recommended as an antimicrobial prophylaxis to prevent infectious complication after transrectal ultrasound-guided biopsy, but the increased appearance of quinolone-resistant organism has raised concerns about the efficacy of quinolone. The current study was performed to evaluate various clinical factors including antimicrobial regimens associated with infectious complication after transrectal ultrasound-guided prostate biopsy.MethodsThe medical records of 5215 patients who underwent a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…[25,26] In addition, we previously reported that the use of third-generation cephalosporins is highly effective in reducing the risk of infectious complications as compared with the use of fluoroquinolone. [27] On the basis of these reports, we also used third-generation cephalosporins in this study. As a result, the absence of infectious complications in all 250 patients in the treatment and control groups in this study accounts for the superior prophylactic effect of third-generation cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…[25,26] In addition, we previously reported that the use of third-generation cephalosporins is highly effective in reducing the risk of infectious complications as compared with the use of fluoroquinolone. [27] On the basis of these reports, we also used third-generation cephalosporins in this study. As a result, the absence of infectious complications in all 250 patients in the treatment and control groups in this study accounts for the superior prophylactic effect of third-generation cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cai et al [26] investigated whether fosfomycin has sufficient efficacy as antibiotic prophylaxis for transrectal prostate biopsy and reported a symptomatic urinary tract infection rate of 1.6%. Other investigators evaluated cephalosporins such as ceftriaxone as an alternative with sufficient relative to flouroquinolones as antibiotic prophylaxis for transrectal prostate biopsy [16,27,28]. In addition, Seitz et al [29] showed a significant reduction in infectious complication with single-shot ertapenem versus ciprofloxacin antibiotic prophylaxis (0.8% vs 14.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Since the European Medicines Agency (EMA) recommended more restrictive use of fluoroquinolones because of potentially permanent side effects, several studies have compared the efficacy of antibiotic prophylaxis for prostate biopsy with different antibiotic regimes [12][13][14][15][16]. To the best of our knowledge, no previous study has explicitly investigated complication rates after prostate biopsy with cefpodoxime as oral antibiotic prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…Due to local bacterial susceptibility to cephalosporins and resistance to quinolones, our study patients were given single dose of oral cefuroxime 500 mg once on the day of procedure. [ 16 ] Patients needing Foley catheterization after biopsy were excluded from the analysis, as catheterization could independently increase risk of infectious complications. The study's endpoint was development of signs and symptoms of infection, as previously defined, within a week of biopsy.…”
Section: Methodsmentioning
confidence: 99%